Exploring ChatGPT to Assist English Language Learners’ Learning Process - Mariafif, Adha; Suwartono, Tono (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2024)
The current study investigates the utilization of ChatGPT to assist students in their language learning process through a descriptive qualitative study. Research data was collected via semi-structured interviews using purposive sampling, targeting five English language education students at a private faith-based university in Purwokerto. The findings indicate that students understand the use of ChatGPT and can effectively use prompts to interact with it. The study also indicates that participants generally use ChatGPT to assist with completing assignments, language learning, and writing their final projects. Participants commonly found that ChatGPT provided inaccurate information and lacked contextual understanding. To address these challenges, they cross-referenced information from ChatGPT with their own knowledge and reliable sources. The study also identified potential challenges such as plagiarism, using ChatGPT for cheating, and dependency on ChatGPT to complete assignments. This study supports the notion that ChatGPT can facilitate and support the language learning process for students.